Suppression of the Karman vortex behind a circular cylinder by ON-OFF control using the pressure gradient - Yusho ISHIKAWA; Itsuro HONDA; Takao SATO (Nihon Kikai Gakkai ronbunshu)
The Karman vortex generated in the flow field around bluff bodies has various negative effects on our daily lives. Therefore, control of the flow field has been studied for suppression of the Karman vortex. Recently, advanced control of the flow field has become possible by the development of fluid analysis technology and computers, and the method using feedback control has been attracting attention. The previous study using model predictive control has the disadvantage that the computational cost is enormous because iterative calculations are performed while predicting future responses. In addition, the previous study using feedback control with the flow velocity cannot completely suppress the vortex because time delay occurs between the time of the flow velocity and the time of control due to detecting the flow velocity behind the bluff body. Therefore, the conventional method can only be applied to flow fields where regular vortices are generated, and is considered impractical. To solve these problems, we propose a method of preventing the occurrence of vortices by controlling at the moment of separation by feedback the pressure gradient on the surface of the bluff body near the separation point. The use of the pressure gradient enables real time detection of separation by its sign, and thus enables control according to the occurrence of the vortex, which may be applicable to flow fields where vortices occur irregularly. In this report, we report the results of control of the flow field around a circular cylinder at low Reynolds number to confirm the effectiveness of the proposed method as a basic study for control in the flow field of high Reynolds number. According to the results of numerical calculation, the proposed method effectively suppresses the Karman vortex generated in the flow field of low to high Reynolds number, confirming the effectiveness of the proposed method.